2023
DOI: 10.1002/adfm.202300012
|View full text |Cite
|
Sign up to set email alerts
|

n‐Type Glycolated Imide‐Fused Polycyclic Aromatic Hydrocarbons with High Capacity for Liquid/Solid‐Electrolyte‐based Electrochemical Devices

Abstract: Currently, n-type small-molecule mixed ionic-electronic conductors remain less explored and their molecular design rules are not mature enough. Herein, two n-type glycolated imide-fused polycyclic aromatic hydrocarbons (IPAHs), d-gdiPDI and t-gdiPDI, are developed to probe the effects of molecular conformation on the electronic, electrochemical, morphological, and coupled ionic-electronic transport properties. It is found that the highly twisted scaffold in d-gdiPDI, compared to the nearly planar one of t-gdiP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Only three reported n-type materials, BBL:PEI, 48 PBFDO 31 (Fig. 3b) and t-gdiPDI 32 (Fig. 5b), work in the depletion mode.…”
Section: Operation Principles Of Oectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only three reported n-type materials, BBL:PEI, 48 PBFDO 31 (Fig. 3b) and t-gdiPDI 32 (Fig. 5b), work in the depletion mode.…”
Section: Operation Principles Of Oectsmentioning
confidence: 99%
“…5b). 32 They aimed to investigate the changes in backbone conformation on OECT performance. DFT calculations revealed that d-gdiPDI exhibits a highly twisted structure, whereas t-gdiPDI possesses a rigid and nearly planar backbone.…”
Section: N-type and Ambipolar Oect Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yue et al. dedicated to developing n‐type small molecule functional materials as highly efficient mixed ionic and electronic conductors in OECTs [27b,32] . We introduced a new series of rigid‐rod electron‐deficient A=A structural small molecules based on naphthalene lactone and its oligomers [33] .…”
Section: Aldol‐condensation‐derived Organic Functional Materialsmentioning
confidence: 99%
“…Very different parameters (such as speed and the type of voltage) have been applied during the measurements of OECTs, and very different results have been obtained in the literature even for similar OECTs (Table S1). , Therefore, it is necessary to clarify the effects of the testing methods and parameters on the measured performance of OECTs.…”
Section: Introductionmentioning
confidence: 99%